The Substantial Form of Legal Products for the Implementation of Criminal Justice during the Covid-19 Pandemic - Tri Margono Budisusilo; Amin Purnawan; Siti Ummu Adillah (Law Development Journal, 2022)
The purpose of this paper is to examine and analyze the study and analysis of the substantial form of legal products for the implementation of criminal justice during the Covid-19 pandemic. This research used a normative juridical method. The conclusion of this research is the Supreme Court issued Circular Letter No. 1 of 2020 concerning Guidelines for the Implementation of Duties During the Prevention of the Spread of Corona Virus Disease 2019 (COVID-19) within the Supreme Court of the Republic of Indonesia and the Judicial Bodies Under it. This letter evaluates and revokes the Circular Letter of the Secretary of the Supreme Court of the Republic of Indonesia Number 1 of 2020 concerning Adjustment of the Work System of Judges and Judicial Apparatuses in Efforts to Prevent the Spread of COVID-19 within the Supreme Court of the Republic of Indonesia and the Judicial Bodies Below, which was issued on March 17, 2020.